2011
DOI: 10.1080/17461391.2010.551410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Big Five personality dimensions on appraisal coping, and coping effectiveness in sport

Abstract: This study investigated the influence of The Big Five personality dimensions (Neuroticism, Extraversion, Agreeableness, Conscientiousness, and Openness to Experience) on the appraisal (intensity, control) of a self-selected stressor, coping, and perceived coping effectiveness. Participants were 482 athletes (male n = 305; female n = 177) who played a variety of sports. Results indicate that The Big Five dimensions influenced coping selection, coping effectiveness, stress intensity, and perceived control of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
79
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 34 publications
17
79
2
1
Order By: Relevance
“…There was also an inverse correlation between the neuroticism trait and social support. The results are in accordance with those from several studies that also found that the personality is an important factor of influence on the selection and use of approach coping strategies (Endler & Parker, 1990;Kaiseler, Polman & Nicholls, 2012). Similar findings were stated by Gilboa et al (1999), who postulated that the cognitive evaluation and the response to the trauma are influenced by personality.…”
Section: Discussionsupporting
confidence: 82%
“…There was also an inverse correlation between the neuroticism trait and social support. The results are in accordance with those from several studies that also found that the personality is an important factor of influence on the selection and use of approach coping strategies (Endler & Parker, 1990;Kaiseler, Polman & Nicholls, 2012). Similar findings were stated by Gilboa et al (1999), who postulated that the cognitive evaluation and the response to the trauma are influenced by personality.…”
Section: Discussionsupporting
confidence: 82%
“…by Wingo et al (2015). The development of these strategies and preferences of their use by adolescent athletes can be related to the protective role of sport during the formation of personality, as it was also described by other authors (Kaiseler, Polman, & Nicholls, 2012). This result also corresponds with the findings of other authors who did research on the subject, like Gaudreau, Nicholls, & Levy (2010), who came to the conclusion in their study that athletes prefer and use differing coping strategies to deal with stress related to competitions.…”
Section: Discussionsupporting
confidence: 79%
“…For instance, a recent study of British gymnasts demonstrated that conscientiousness was positively associated with athletes' quality of preparation in the lead up to competition and emotional stability was positively associated with effective coping during competition (Woodman, Zourbanos, Hardy, Beattie, & McQuillan, 2010). Other research has explored the effect of personality on psychological states such as aggressiveness (Trninić, Baranĉić, & Nazor, 2008) and coping functions (Allen, Frings, & Hunter, 2012;Allen et al, 2011;Kaiseler, Polman, & Nicholls, 2012). These studies show that athletes with low levels of agreeableness, extraversion, and/or emotional stability are more prone to aggressive behaviours, athletes with low levels of openness and/or emotional stability are more prone to using avoidance coping strategies, and athletes with high levels of conscientiousness, extraversion, and/or emotional stability are more prone to using problem-focused coping strategies.…”
Section: Personality and Performance In Sportmentioning
confidence: 99%